ANALYSIS OF ORIGINAL LOCAL GOVERNMENT REVENUE (PAD) ON THE FINANCIAL PERFORMANCE OF KEBUMEN REGENCY BEFORE AND DURING THE COVID-19 PANDEMIC - Sabrina, Nayla; Nugraheni, Agustina Prativi (Transpublika Publisher, 2022)
This research seeks to find out how the financial performance of Kebumen Regency is seen from the Original Local Government Revenue before and during the covid-19 pandemic. The COVID-19 pandemic that is happening in Indonesia caused a change in Kebumen Regency's PAD due to a decline in tourism sector income, as well as a number of hotel and restaurant taxes in Kebumen Regency. This research is a qualitative study with a descriptive analysis method through secondary data in the form of a Kebumen Regency Budget Realization Report from 2018-2021. The year was taken because 2018-2019 was the year before the emergence of Covid-19, while 2020-2021 was the year where Covid-19 attacked all Indonesian people. The result of this study indicates that although the Regional Revenue of Kebumen Regency has decreased, Covid-19 has no effect on the financial performance of Kebumen Regency.